Importance of cephalographs in diagnosis of patients with sleep apnea - Nimma Vijaya Laxmi; Harshavardhan Talla; Deepika Meesala; Shakuntala Soujanya; Nithya Naomi; Manasa Poosa (Wolters Kluwer Medknow Publications, 2015)
Introduction: Obstructive sleep apnea (OSA) is considered to be a potentially life threatening disorder, which is characterized by repeated collapse of the upper airway during sleep with cessation of breathing. The cephalometric method despite being a static, two-dimensional evaluation of dynamic three-dimensional structures of the head and neck is useful in diagnosing patients with OSA, as they have shown that significant differences exist between asymptomatic controls and patients with OSA. Aims and Objectives: This study is designed to compare and validate the craniofacial morphology in patients with OSA using lateral cephalometry in both upright and supine position. Materials and Methods: Sixty subjects participated in the study of which 30 were patients with OSA diagnosed by questionnaire and 30 were healthy control group with age range of 25-45 years. Results: The study group demonstrated an increased ANB, mandibular plane angles (GoGn-SN), lower anterior facial height which are statistically significant with a significant P < 0.05. Significant decrease in posterior airway space, increased soft palate length, tongue length, and thickness suggesting reduced airway space in supine posture. Conclusion: Evaluation of craniofacial morphology in OSA patients using lateral cephalometry helps in recognizing the morphological changes induced by altered sleep pattern and for appropriate treatment planning.